Revolutionizing preoperative nutritional assessment: a multi-tool approach to predicting surgical complications in GI patients - Siva Sandeep, Katamsetti; Kakade, Smita Vikram (International Journal of Research in Medical Sciences, 2025)
Background: Malnutrition significantly impacts surgical outcomes, particularly in gastrointestinal (GI) surgeries. Traditional single-tool nutritional assessments often fail to identify all at-risk patients, underlining the need for a more comprehensive approach. This study aims to evaluate the efficacy of an integrated nutritional assessment approach, combining the malnutrition universal screening tool (MUST), subjective global assessment (SGA), and nutritional risk index (NRI), in improving the prediction of postoperative outcomes in GI surgery patients. Methods: We conducted a comparative analysis involving patients undergoing GI surgeries, each patient was assessed preoperatively using MUST, SGA, NRI individually, and also with a combined integrated scoring approach. The predictive performance of each method was evaluated against postoperative outcomes. Key outcomes measured included hospital stay length, re-exploration rates, anastomotic leak rates, and mortality rates. Sensitivity, specificity, and predictive accuracy were analyzed through receiver operating characteristic (ROC) curve assessments. Results: The integrated assessment more accurately identified high-risk patients who experienced adverse outcomes such as longer hospital stays, higher re-exploration rates, and increased anastomotic leaks. This reflects improved predictive capability rather than causation. While the integrated method showed higher mortality rates, this was attributed to the accurate identification and inclusion of high-risk patients. The integrated approach demonstrated a balanced sensitivity (80%) and specificity (52%), with superior predictive accuracy (AUC=0.701) over any single-tool assessment. Conclusion: The integration of MUST, SGA, and NRI in preoperative nutritional assessments for GI surgeries provides a more accurate, reliable, and holistic evaluation of nutritional risk, leading to better preoperative optimization and this eventually improves post operative outcomes. This study supports the adoption of integrated nutritional assessments as a standard practice in preoperative protocols, suggesting potential for broader application across various surgical disciplines.